(untitled) (Medico Legal Update, 2021)
This study aimed to identify the relationships between body image perception and body esteem and sexual assertiveness of 296 female college students of university in Chungnam province: 150 nursing and 146 non-nursing students. Data were collected using a self-administered questionnaire from November 1 to September 10, 2018. The IBM SPSS 20.0 program was used to analyze collected data, including descriptive statistics, t-test, one way ANOVA (Scheffe test for post-hoc) and Pearson’s correlation. Sexual assertiveness did not differ between nursing and non-nursing students. In nursing students, the higher the appearnace esteem, the higher the sexual assertiveness; however, differences in sexual assertiveness according to body image perception were not significant. In non-nursing students, the higher the appearnace esteem, attribution esteem, and body weight esteem, the higher the sexual assertiveness, which was also higher in students who underestimate their body than those who did not. These results indicated that appearance esteem of female students were related to sexual assertiveness. Therefore, various interventions to increase the appearance esteem and promote positive perception about their body should be provieded to increase the sexual assertiveness of female college students.